Զապէլ Եսայեանին ուղղուած յայտնի եւ անյայտ նամակներ (1907-1908 եւ 1922-1927) - Մատթէոսեան, Վարդան (տպ. Atlas)
In 1972 Armand and Arsen Pushman, sons of the celebrated Armenian American painter Hovsep Pushman (1877-1966), donated his collection of letters to the Museum of Literature and Art “Yeghishe Charents” of Armenia. The donation was received by philologist Babken Chookaszian (1923-1997), then deputy director of the Matenadaran of Yerevan, who was visiting the United States. The collection included 129 letters addressed to various writers, artists, and public figures. Chookaszian, who published various samples of that collection in 1973, stated that the collection was numbered and paginated in alphabetical order, and that the last number was 240, but that the whereabouts of the remaining letters were unknown.
Keywords: Նամակագրութիւն